Neuroendocrine Neoplasms of the Gallbladder: A Clinicopathological Analysis of 13 Patients and a Review of the Literature - Pengyan Wang; Jingci Chen; Ying Jiang; Congwei Jia; Junyi Pang; Shan Wang; Xiaoyan Chang (Gastroenterology Research and Practice)
Objectives. Mixed neuroendocrine–non-neuroendocrine neoplasms (MiNENs) are rare gallbladder neuroendocrine neoplasms (GB-NENs). This study is aimed at investigating the clinicopathological features of GB-NENs and identifying prognostic factors related to overall survival (OS) of GB-MiNENs. Methods. The clinical data and pathological features of 13 patients with GB-NENs in our hospital were retrospectively reviewed. Additionally, 41 GB-MiNENs cases reported in English literature were reviewed and survival analysis was performed. Results. The mean age of thirteen patients (6 males and 7 females) with GB-NENs was 57.2 years (range: 35-75 years). Two patients were diagnosed with NET grade 1 (G1), two patients with NEC (large cell/small cell=1/1), and nine patients with MiNENs. Of these 9 patients with MiNENs, 8 had composite tumors and 1 had amphicrine carcinoma. Microscopically, the adenocarcinoma component was located in the surface mucosa, and the neuroendocrine component was in the area of deep invasion, liver infiltration, and lymph node metastasis. Total analysis of 41 GB-MiNENs showed that patients were mainly elderly women (female/male ratio, 2.4 : 1.0; median age, 60 years). Kaplan-Meier’s analysis demonstrated that liver metastasis and TNM stage III-IV were associated with decreased OS (P<0.05), whereas age, sex, tumor size, grade of the neuroendocrine component, lymph node metastasis, and adjuvant chemotherapy were not significantly prognostic indicators of OS. Multivariate analysis identified liver metastasis (hazard ratio=4.262, 95%confidence interval=1.066‐17.044, P=0.040) as an independent unfavorable prognostic factor. Conclusions. GB-MiNENs were the most common type of GB-NENs in our case series, and neuroendocrine components exhibited more aggressive lymph node metastasis and local invasion than adenocarcinoma. Liver metastasis was a poor prognostic indicator in GB-MiNENs patients.